2-Amino-6-methylbenzothiazole as corrosion inhibitor for low carbon steel in acidic solution: Experimental and theoretical studies - Klodian Xhanari; Muhamed Farruku; Avni Berisha; Bujar Seiti; Kledi Xhaxhiu; Efrosini Kokalari; Alketa Lame (Results in Chemistry)
The corrosion susceptibility of S235 steel samples in 1 M HCl solution, with and without addition of 2-amino-6-methylbenzothiazole (AMBT) was evaluated using weight loss (WL), chronopotentiometry, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization (PD) techniques. The corrosion inhibition efficiency of AMBT was investigated at 298 to 318 K, with and without addition of 0.5 wt.% KI. The highest corrosion inhibition efficiency (i.e. 83.30%) was achieved upon addition of 5 mM AMBT. PD curve measurements after 24 h immersion revealed that AMBT behaves as a mixed-type inhibitor, predominantly affecting the cathodic corrosion reaction. Thermodynamic calculations showed that AMBT adheres to the Langmuir adsorption isotherm. Attenuated total reflectance Fourier transform infrared (ATR-FTIR) was used to confirm the adsorption of AMBT, while its influence on the morphology of the S235 steel samples was also investigated by scanning electron microscopy (SEM). Density Functional Theory (DFT) calculations, along with Monte Carlo (MC) and Molecular Dynamics (MD) simulations, were employed to investigate AMBT’s corrosion inhibition behaviour at the molecular level. The simulations confirmed that AMBT strongly adsorbs on the Fe(110) surface through a combination of physisorption and chemisorption mechanisms. This study offers detailed insights into AMBT’s effectiveness as a corrosion inhibitor.